Human occupational intensity and palaeoecology at Klasies River from MIS 5–3: Preliminary taphonomic analyses of faunal remains from the Deacon and Wurz excavations - Reynard, Jerome P. (Frontiers in Earth Science, 2022)
Klasies River is a key site in understanding the behaviour of coastal foragers in the southern Cape of South Africa. Faunal remains from Klasies River, recovered from an almost 70,000 year sequence over the Late Pleistocene, are a valuable dataset in investigating subsistence and occupational dynamics, yet few taphonomic studies have been conducted on the fauna from Klasies River. Here, the first taphonomic analysis of faunal remains from the Deacon and Wurz excavation is presented. The aim of this paper is to link occupational patterns during the Late Pleistocene at Klasies River with coastal ecology using taxonomic data from previous studies, and recently analysed taphonomic data. Taphonomic analyses of samples from the MSA II Lower, the Howiesons Poort and the MSA III periods were used to examine occupational intensity based on proportions of anthropogenic and zoogenic bone surface modification, trampling marks, transverse fractures and faunal density. Declining foraging efficiency or subsistence intensification was also investigated using indicators for expanded diet breadth (e.g., small fauna exploitation and increases in juveniles), more intensive marrow extraction and evidence for greater foraging distances. Herbivore functional types and dietary preferences were investigated using taxonomic data and these show three main ecological phases at Klasies River: the MSA I; the upper and lower MSA II; and the HP and MSA III phases. Taphonomic data point to increased occupational intensity in the MSA II Lower, with subsistence intensification also more evident here than in other periods. Trampling data suggest occupational intensity was greater in the earlier Howiesons Poort than later phase, with little evidence of declining foraging efficiency then. The data indicate that, while humans contributed significantly to the MSA III assemblage, carnivores were the main accumulators here suggesting lower occupational intensity in this phase. The results of this study show a possible link between increased occupational intensity and declining foraging efficiency at Klasies River but larger taphonomic samples are needed to explore this relationship further.